The Influence of Parenting Style And Self-Control on The Character of Adolescent Responsibility - Vidya Halima Thusyadia; Bambang Sumardjoko (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the influence of parenting styles and self-control on adolescents' sense of responsibility.Methodology: A quantitative approach with an ex post facto design was employed,. The sampling technique used is proportional stratified random sampling. The study population consists of 711 grade 11 students at SMAN 1 Kartasura and SMAN 2 Sukoharjo, and the study sample consists of 256 students.Results: The simultaneous regression analysis shows that parenting style and self-control jointly have a significant effect on adolescents' responsibility (F = 161.863, p < 0.05). Self-control emerged as the strongest predictor, contributing more substantially to the variance of responsibility compared with parenting style.Applications/Originality/Value: This study can be applied in the field of Civic Education by quantitatively proving that Self Control is a more dominant predictor than Parenting Style in explaining the formation of Responsibility in Adolescents. This finding confirms that the internalization of national values and civic responsibility is highly dependent on an individual's capacity for self-regulation. Its applied value lies in concrete recommendations for teachers and civic education curriculum developers to design integrative intervention programs that not only teach values but also explicitly prioritize training in Self-Control skills and impulse management.